Além dos 60: moradores de Coimbra e São Paulo - Mariz, Maria Elisa de Almeida (2009)
This paper comprises a qualitative social research and intends to apprehend the motivations and life perspective of people who are sixty years old or more by interviewing 20 retired person that are still working and who live either in São Paulo or in Coimbra. It aims to understand the elements of interviewee s health life regarding job, leisure, culture, entertainment, travels, hobbies, physical activities as well as their preferences and affinity with their relevant cities. The growth of people who are sixty years old or more, in absolute and relatively parameters, is a global phenomenon which has been boosting very fast. Brazil, which was recently considered a young country, is already classified as the 6th country of the world in terms of ageing rate and has 10% of its population with sixty years of age or more. Applied to São Paulo City, such ageing rate corresponds to one million people. The focus of this paper is to analyze under a different point of view such population share the ones who are sixty years old or more which importance results not only from their growth but mainly from the potential they represent in terms of knowledge, culture, wisdom and experience. The interviews have revealed a new way of life, on which people who are sixty years old or more enjoy their old age considering it as a moment full of opportunities, possibilities and transformation on every aspect of their lives, mainly on their professional activities, bearing in mind that many of them restarted working after retiring. The great majority of the interviewees are healthy, some of them suffer from age illness. Although, all of them showed willingness to enjoy, intensely, their life and to look for alternatives to do it, by running away of boredom, updating themselves, finding an purpose to life, networking young people and finding their own wellbeing